Optimization of coagulation-flocculation parameters using a photometric dispersion analyser - S. R. Ramphal; M. S. Sibiya (Drinking Water Engineering and Science, 2014)
The size and structural characteristics of floc particles are important design and control parameters in water treatment and should be rapidly monitored with a reasonable amount of accuracy. In this study, a photometric dispersion analyser (PDA) coupled to standard jar test experiments was used to optimize coagulation-flocculation parameters while monitoring floc size and structure as well as the rate of floc formation during coagulation using alum. The optimal coagulation conditions were as follows: sample pH 8; alum dosage, 3 mg L−1 as Al3+; G value, 172 s−1; rapid mixing time, 20 s. These conditions resulted in unstable treated water having a calcium carbonate precipitation potential (CCPP) of −15 mg L−1 as CaCO3 and required a slaked lime dosage of 17 mg L−1 as CaCO3 to equilibrate CCPP to acceptable levels. PDA data revealed that aggregation rate and steady-state variance are primary parameters as both have substantial influence on coagulation-flocculation efficiency. However, the average steady state ratio, although an important parameter, had a lessened impact on coagulation-flocculation efficiency. The results of this study showed that the PDA instrument is an important tool in coagulation kinetic studies and can be employed as an additional tool in the optimization of coagulation conditions.